Prevalence of Congenital Anomalies on Routine Ultrasound Examination of Second and Third Trimester Pregnancy - Ridwan Abdullah Putra (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran)
Objective:This study aims to determine the prevalence and characteristics of congenital anomalies and maternal demographic of second and third trimester pregnancy as a basis for the planning and management of congenital anomalies in the future pregnancy.Method: This is a descriptive-retrospective study conducted at Cikalongwetan General Hospital by collecting data obtained from the obstetrics and gynecology outpatient and inpatient register book from January 1st through December 31st 2018.Results: Ultrasound examination was performed on 2572 patients at second and third trimester of pregnancy. 37 cases (1.44%) of congenital anomalies was found. Single congenital anomalies was found in 29 cases (78.38%), while 8 cases were found with multiple anomalies (21.62%). Based on organ anomaly, defects in the central nervous system was the most common with 15 cases (40.54%), followed by gastrointestinal system in 8 cases (21.62%). The gestational age related to CA was found most common in the third trimester with 21 cases (56.76%), while deceased fetus (IUFD) was found in 11 cases (29.73%).Conclusion: This study is expected to foster early awareness regarding regular antenatal care and the importance of ultrasoud examination so can help in primary prevention of disability and reducing perinatal mortality and morbidity.Key words: Prenatal, Congenital anomalies, UltrasonographyAbstrakTujuan: Menentukan prevalensi kejadian, jenis kelianan kongenital dan data demografi ibu saat trimeset dua dan tiga selama periode penelitian sebagai dasar dan bahan pertimbangan dalam perencanaan dan manajemen bayi dengan kelainan bawaan selanjutnya.Metode: Penelitian retrosepektif dengan cara mengumpulkan data yang diperoleh dari buku register kunjungan poli dan rawat inap Kebidanan dan Penyakit Kandungan RSUD Cikalongwetan selama periode 1 Januari – 31Desember 2018.Hasil: Pada penelitian ini telah dilakukan pemeriksaan ultrasonografi sebanyak 2572 ibu hamil trimester dua dan tiga, ditemukan kelainann kongenital 37 kasus (1,44%). Kelainan kongenital tunggal 29 kasus (78,38%), 8 kasus kelainan ganda (21,62%). Berdasarkan kelainan organ, cacat pada sistem saraf pusat menempati urutan pertama15 kasus (40,54%) diikuti oleh kelainan pada sistem pencernaan 8 kasus (21,62%) dan sistem saluran kemih4 kasus (16,22%) dan lainnya 12 kasus (32,43%). Usia kehamilan dari kelainan kongenital yang paling sering ditemukan pada trimester ketiga 21 kasus (56,76%) dengan janin yang telah meninggal (IUFD) sebanyak 11 kasus (29,73%).Kesimpulan: Penelitian ini diharapkan dapat menumbuhkan kesadaran sejak dini mengenai perawatan antenatal yang teratur dan pentingnya pemeriksaan ultrasonografi sehingga dapat membantu dalam pencegahan primer kecacatan serta mengurangi angka kematian dan morbiditas perinatal.Kata kunci: Prenatal, Kelainan kongenital, Ultrasonografi